2014
DOI: 10.1038/cdd.2014.189
|View full text |Cite
|
Sign up to set email alerts
|

p53 suppresses muscle differentiation at the myogenin step in response to genotoxic stress

Abstract: Acute muscle injury and physiological stress from chronic muscle diseases and aging lead to impairment of skeletal muscle function. This raises the question of whether p53, a cellular stress sensor, regulates muscle tissue repair under stress conditions. By investigating muscle differentiation in the presence of genotoxic stress, we discovered that p53 binds directly to the myogenin promoter and represses transcription of myogenin, a member of the MyoD family of transcription factors that plays a critical role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 67 publications
0
42
0
Order By: Relevance
“…Importantly, inhibition of p53 partially rescued the differentiation defects of hypoxia-treated myoblasts, indicating that hypoxia regulates Bhlhe40 at least partially through p53. In a recent study, p53 has been reported to inhibit the transcription of Myog directly by binding to the promoter of Myog under genotoxic stress (39). Our study sheds light on an alternative avenue through which p53 regulates Myog.…”
Section: Discussionmentioning
confidence: 89%
“…Importantly, inhibition of p53 partially rescued the differentiation defects of hypoxia-treated myoblasts, indicating that hypoxia regulates Bhlhe40 at least partially through p53. In a recent study, p53 has been reported to inhibit the transcription of Myog directly by binding to the promoter of Myog under genotoxic stress (39). Our study sheds light on an alternative avenue through which p53 regulates Myog.…”
Section: Discussionmentioning
confidence: 89%
“…While myogenin is important for myotube terminal differentiation and fusion, its expression has been show to inhibit myoblast responsiveness to epidermal growth factors (50). Additionally, decreased myogenin expression may represent a myogenic checkpoint to ensure genetic stability in differentiated cells and proper regeneration (51). Taken together, these data suggest that pathogenic Tregs may cause a defective myogenic differentiation program through modulating macrophage subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, analysis of the regulation of key myogenic regulatory factors by p53 was examined under irradiation stress. The results indicate a direct role for p53 transcriptional repression of myogenin, with the likely purpose of ensuring adequate time for DNA damage repair and chromosomal segregation [92]. Furthermore, a time course was evaluated leading to the conclusion that a two-phase conditional regulation by p53 exists.…”
Section: The Role Of P53 In Mediating Oxidative Stress Imposed By Radmentioning
confidence: 96%
“…The role of p53 on skeletal muscle differentiation following DNA damage is a field of interest because of its implications for the regenerative capacity of muscle. Previous work has revealed that p53 maintains the genetic stability of mouse embryonic stem (MES) cells following DNA damage by repressing Nanog, a cancer-stem cell marker, to then regulate and promote differentiation [92,93]. Regulation of MES cells is of key importance since skeletal muscle originates through myogenesis from the mesoderm, one of the three primary germ layers.…”
Section: The Role Of P53 In Mediating Oxidative Stress Imposed By Radmentioning
confidence: 99%
See 1 more Smart Citation